Odpowiedź :
a) (x-5)² = (x- √3) (x+√3)
x²-10x+25=x²-3
x²-10x-x²=-3-25
-10x=-28| :(-10)
x=2,8
b) (x+1)² + (x-2)² = 2(x-1)(x+1)
x²+2x+1+x²-4x+4=2(x²-1)
2x²-2x+5=2x²-2
2x²-2x-2x²=-2-5
-2x=-7 |: (-2)
x=3,5
x²-10x+25=x²-3
x²-10x-x²=-3-25
-10x=-28| :(-10)
x=2,8
b) (x+1)² + (x-2)² = 2(x-1)(x+1)
x²+2x+1+x²-4x+4=2(x²-1)
2x²-2x+5=2x²-2
2x²-2x-2x²=-2-5
-2x=-7 |: (-2)
x=3,5
a) (x-5)²=(x-√3)(x+√3)
x²-10x+25=x²-3
x²-10x-x²=-3-25
-10x=-28/÷(-10)
x=2,8
b)(x+1)²+(x+2)²=2(x-1)(x+1)
x²+2x+1+x²-4x+4=2(x²-1)
2x²-2x+5=2x²-2
2x²-2x-2x²=-5-2
-2x=-7/÷2
x=-3,5
x²-10x+25=x²-3
x²-10x-x²=-3-25
-10x=-28/÷(-10)
x=2,8
b)(x+1)²+(x+2)²=2(x-1)(x+1)
x²+2x+1+x²-4x+4=2(x²-1)
2x²-2x+5=2x²-2
2x²-2x-2x²=-5-2
-2x=-7/÷2
x=-3,5